A study on factors that influenced investors to invest in CIMB Unit Trust / Norul Isma Izan Johari - Johari, Norul Isma Izan (2010)
Unit trust is a collective investment scheme that pools the savings of a large number of investors. The study of this report is about CIMB unit trust. Presently the best performing bank in Malaysia, the CIMB group continues to grow by means of portfolio expansion locally and overseas, as well as through mergers and acquisitions. This research objective to identify the suitable strategies based on actual investor’s needs and wants for CIMB Unit Trust Funds in order to compete in the unit trust industry. To achieve its investment objective whether it is long-term growth or capital appreciation or anything in between the fund’s manager invests in securities he or she believes will provide the results the fund seeks. For CIMB Berhad, they need to plan strategies in order to maintain their market share and to increase profit. This study focusing on CIMB investors whose are currently having investment in CIMB Berhad. Based on the research done, the factors that are influences the investors to invest in CIMB fund consist of four factors which is effectiveness of sales force, strength of the CIMB fund, brand name of CIMB and lastly the financial performance of CIMB funds. Based on the result that from the entire test that had executed, researcher identified that sales force is the best factors that influences the investors to invest CIMB’s funds. The rank followed by the financial performance which investors will look forward in order to invest in mutual funds. Next is the strength of CIMB funds, which consist of size of funds, objectives of funds and also the number of funds. And lastly, the brand name of CIMB which is less influencing the investors to invest in CIMB funds.